1994
DOI: 10.2172/10168347
|View full text |Cite
|
Sign up to set email alerts
|

An empirical investigation of operator performance in cognitively demanding simulated emergencies

Abstract: This report documents the results of an empirical study of nuclear power plant operator performance in cognitively demanding simulated emergencies. During emergencies operators follow highly prescriptive written procedures. The objectives of the study were to understand and document what role higher-level cognitive activities such as diagnosis, or more generally 'situation assessment,' play in guiding operator performance, given that operators utilize procedures in responding to the events. The study examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(34 citation statements)
references
References 0 publications
0
33
0
1
Order By: Relevance
“…The ISLOCA scenario is referred from nuclear regulation/control room-6208 (NUREG/CR-6208) [28]. The ISLOCA scenario was designed to be difficult from the point of view of situation assessment.…”
Section: Message Is Not Transmitted To the Receivermentioning
confidence: 99%
“…The ISLOCA scenario is referred from nuclear regulation/control room-6208 (NUREG/CR-6208) [28]. The ISLOCA scenario was designed to be difficult from the point of view of situation assessment.…”
Section: Message Is Not Transmitted To the Receivermentioning
confidence: 99%
“…Following these developments, and continuing experience with human actions associated with misunderstandings by operators in responding to unusual plant conditions, developments took place to create newer HRA models that use as their basis a more complete understanding of the interactions between people and the systems. For example, later work by Woods et al [22], Hollnagel [23,24], Roth, et al [25] and Reason [18] all added significantly to the explanation of how people can be led to misunderstand the nature of events. This explanation underlies several of the more recent methods like ATHEANA [3] and CAHR (Sträter [26]; Sträter and Bubb [27]).…”
Section: What Do the Behavior Sciences Say About The Causes Of Unsafementioning
confidence: 99%
“…While procedures (whether written or memorized through training) provide a structured support to operators, experiments (Roth et al [25]) have shown that they are, at best, an initial basis for action but operators must reassess the guidance in light of the actual plant conditions; even for the symptom-based procedures developed after Three Mile Island. In other words, while procedures are written using certain assumptions about the course that an off-normal condition will take, there are many opportunities for the plant to behave differently from the assumptions underlying the procedures.…”
Section: Decision Making In Nuclear Power Plant Operationsmentioning
confidence: 99%
See 1 more Smart Citation
“…prescribed tasks in EOPs) and a dynamic process (i.e. the nature of an on-going situation) [1]- [3]. From the existing human reliability analysis (HRA) method, the effect of procedures on human performance has been recognized as one of the most important performance shaping factors (PSF) [4]- [6].…”
Section: Introductionmentioning
confidence: 99%